Buy, Use, Make—A taxonomy of sustainable consumption practices - Bradley, Karin; Hilliard, William; Parekh, Vishal (Frontiers in Sustainability, 2025)
In policy debates around sustainable consumption, the term is often associated with buying products or services that have lower environmental impact when compared with mainstream options. This paper contributes to the growing body of research that seeks to nuance understandings of sustainable consumption by providing a taxonomy structured into three ‘types' of sustainable consumption practices: (1) buying, (2) using and (3) making. The taxonomy highlights that sustainable consumption concerns not only the decisions made around the acquisition of a product or service, but also how products and resources are maintained, reused, repaired, shared and enabled—while also considering wider socio-environmental aspects such as community empowerment. The relevance for policy lies in the argument that sustainable consumption goes beyond the buying type—enacted through, for example, public procurement or promotion of eco-labeling—to also include the using and making types, i.e. public policy that facilitates sharing, making and repairing beyond market-relations.